2020
DOI: 10.3390/soc10040096
|View full text |Cite
|
Sign up to set email alerts
|

Recognition and Justice? Conceptualizing Support for Women Whose Children Are in Care or Adopted

Abstract: This paper examines the views of mothers who have experienced (or are judged to be at risk of) recurrent removal of children into care or adoption. Drawing on their accounts of working with an intensive 18 month support program called Pause, we argue for the relevance of conceptualizing policy and practice with reference to Honneth’s theory of recognition and Fraser’s arguments about the need to address misrecognition through redistribution, attending to gendered political and economic injustice. The analysis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 31 publications
1
8
0
Order By: Relevance
“…Navigators were seen not simply to possess ‘lay’ knowledge but considered a skilled practitioner or a “professional ex-” (Brown, 1991). This enabled individuals to move, sometimes cautiously, from a devalued and marginalised identity to a more positive social identity in which they were recognised as competent, knowledgeable and highly regarded (Boddy and Wheeler, 2021; Ehrlich et al, 2019): “I’m a product of the lived experience route, I’ve got my own experiences of the criminal justice system, the mental health services, to a degree homelessness, I did sofa surf and I had my own addictions through cocaine and cannabis. I would have been a beneficiary five years ago…so taking that step to paid employment with [service], it was an anxious time for me but I’d been told that I was ready for it…a person like me doesn’t get that many opportunities to work for a council” (N7) …”
Section: The ‘Value’ Of Experiential Knowledgementioning
confidence: 99%
See 1 more Smart Citation
“…Navigators were seen not simply to possess ‘lay’ knowledge but considered a skilled practitioner or a “professional ex-” (Brown, 1991). This enabled individuals to move, sometimes cautiously, from a devalued and marginalised identity to a more positive social identity in which they were recognised as competent, knowledgeable and highly regarded (Boddy and Wheeler, 2021; Ehrlich et al, 2019): “I’m a product of the lived experience route, I’ve got my own experiences of the criminal justice system, the mental health services, to a degree homelessness, I did sofa surf and I had my own addictions through cocaine and cannabis. I would have been a beneficiary five years ago…so taking that step to paid employment with [service], it was an anxious time for me but I’d been told that I was ready for it…a person like me doesn’t get that many opportunities to work for a council” (N7) …”
Section: The ‘Value’ Of Experiential Knowledgementioning
confidence: 99%
“…Support on this basis can be understood as emblematic of a sense of equality, solidarity and reciprocity between navigator and service user that others have identified as important in support work more generally (Boddy and Wheeler, 2021; Fox, 2020). Experiential knowledge was also felt to retain an authority that credited navigators with a greater “respect” placing them in a more favourable position (than other front-line practitioners and professionals) to motivate user engagement and positive change.…”
Section: The ‘Value’ Of Experiential Knowledgementioning
confidence: 99%
“…In the UK, Pause (https://www.pause.org.uk), a support programme for women who have had children removed, has for some years made LARC use a condition of attendance. Whilst attending Pause is nominally optional, as some attendees recognise, their dependency on the programme to improve their lives and increase their chances of seeing existing or keeping future children, means that LARC acceptance is not a choice but an imperative (Boddy & Wheeler, 2020). Although, recently, this condition has been expanded to include use of non-LARC methods of contraception (BPAS, 2021), the change was made only after criticism of their approach.…”
Section: Demonised Behavioursmentioning
confidence: 99%
“…As well as being trauma informed in its relational model of working, Pause also helps women to stabilise their lives by providing support to take up benefits, address debt, access safe and secure housing and offers flexible financial support (Boddy et al, 2020). A recent evaluation has shown that women who have worked with Pause have greater housing and financial security (Boddy et al, 2020) and women reported how important it was for their practitioners to help them to navigate complex welfare systems, suggesting that recognition of socio‐economic disempowerment helped these women to develop trusting relationships with professionals (Boddy & Wheeler, 2020).…”
Section: Systemic Adversitymentioning
confidence: 99%